(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2011)
Anne and Patrick Poirier’s artistic research, particularly on the theme of memory, has been nourished by the ancient ruins that they had the occasion to study during several trips. A major influence came to them from Villa Medici and from Hadrian’s Villa, which they repeatedly visited in 1977.